Penerapan Metode ORESTE untuk Pemilihan Smartphone Gaming Terbaik di Kelas Menengah Berdasarkan Konsumen - Samantha Arta Sinuhaji; Sandy Hardiansyah; Candra Harapan Simanjuntak; Saifullah Saifullah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to help consumers choose the best mid-range gaming smartphone using the ORESTE (Organisation, Élimination et Choix Traduisant la Réalité) method. This method is applied to provide recommendations based on important criteria, such as processor performance, RAM capacity, screen quality, battery life, and price. The first stage of this study is problem identification that focuses on choosing the best mid-range gaming smartphone. Next, the determination of alternatives and relevant criteria is carried out, followed by data collection using a questionnaire distributed to 78 respondents. The collected data is then analyzed using the ORESTE method to calculate the global ranking of each alternative. The results of the analysis show that Samsung smartphones are in first place as the best choice based on the ranking obtained from each criterion. The use of the ORESTE method allows systematization in decision-making, by considering the weight and priority of relevant criteria. This study contributes to helping consumers make more objective and targeted decisions in choosing a gaming smartphone that suits their needs and preferences. In addition, this study is also expected to be a reference for smartphone manufacturers in understanding consumer preferences and improving the quality of their products. Thus, the results of this study are not only beneficial for consumers, but also for the smartphone industry as a whole.